2022
DOI: 10.3390/horticulturae8090831
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Potato (Ipomoea batatas L.) Response to Incremental Application Rates of Potassium Fertilizer in Mississippi

Abstract: Potassium (K) fertilization is a crucial component of sweet potato (Ipomoea batatas L.) production. The basis for K fertilizer recommendations in sweet potato production varies greatly and relies on studies conducted in the late 1950s–1970s. Changes in agronomic practices and increasing costs emphasize the need to revisit fertilizer recommendations. A field experiment was conducted to investigate the impact of seven different K fertilizer (K2O) application rates on sweet potato storage root yield, tissue K con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Fertilization with potassium (K) is an essential step in the formation of sweet potatoes. K is necessary for photosynthesis, transport of sugar, movement of water and nutrients, synthesis of protein, and formation of starch in sweet potatoes (Harvey et al, 2022). This study found that increasing the potassium fertilizer rate promoted vegetative growth as measured by leaf area and shoot dry weight.…”
Section: Discussion Discussion Discussionmentioning
confidence: 71%
“…Fertilization with potassium (K) is an essential step in the formation of sweet potatoes. K is necessary for photosynthesis, transport of sugar, movement of water and nutrients, synthesis of protein, and formation of starch in sweet potatoes (Harvey et al, 2022). This study found that increasing the potassium fertilizer rate promoted vegetative growth as measured by leaf area and shoot dry weight.…”
Section: Discussion Discussion Discussionmentioning
confidence: 71%
“…The area planted and the yield of I. batatas in the US has increased by 65 and 35%, respectively, in the last 20 yr (2000–2020) (USDA 2021). This increase in I. batatas production is mainly due to the expansion of areas planted in California, Louisiana, Mississippi, and North Carolina (Johnson et al 2015; Harvey et al 2022). Florida also has become a prominent producer with nearly 2,500 ha of I. batatas , most in Miami-Dade and Suwannee counties (Alam 2021).…”
mentioning
confidence: 99%